DEVELOPMENT OF INTERACTIVE PBL-BASED E-LKPD TO ENHANCE MATHEMATICAL LITERACY ON ARITHMETIC SEQUENCES AND SERIES - Elina Hasna Fauziya; Hanifah Nurus Sopiany (Universitas Sembilanbelas November Kolaka, 2026)
This study developed an interactive electronic student worksheet (E-LKPD) based on Problem-Based Learning (PBL) to enhance Grade X students' mathematical literacy on arithmetic sequences and series and evaluated its validity, practicality, and effectiveness. The study employed research and development using the ADDIE model. Three material experts and three media experts assessed product validity, two mathematics teachers and 36 students assessed practicality, and 36 students completed mathematical-literacy pretests and posttests. Material validity covered content eligibility, presentation, and language, whereas media validity covered visual design, technical quality, and alignment with learning. Practicality was examined through teacher ratings of learning design, visual communication, and benefits and student ratings of cognitive, affective, and conative responses. The product achieved material- and media-validity scores of 98% and 93%, respectively. Teacher and student practicality scores were 90% (very practical) and 79% (practical). The mean mathematical-literacy score increased from 30.58 to 78.36, with an N-Gain of 0.69 (moderate) and a significant paired-samples t-test result (p .001). Therefore, the interactive PBL-based E-LKPD is valid, practical, and effective for supporting mathematical literacy on arithmetic sequences and series.